483 Association of COVID-19 inflammation with activation of the C5a-C5aR1 axis. (9th November 2020) - Demaria, Olivier; Carvelli, Julien; Benmansour, Nassima Chouaki; Fares, Joanna; Batista, Luciana; Thibult, Marie-Laure; Morel, Ariane; Carpentier, Sabrina; Remark, Romain; Represa, Agnes; Vely, Frederic; Ebbo, Mikael; et al.
Abstract : Background: Coronavirus disease 2019 (COVID-19) is a new pandemic disease caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The C5a anaphylatoxin and its receptor C5aR1 (CD88) play a key role in the initiation and maintenance of several inflammatory responses, by recruiting and activating neutrophils and monocytes in the lungs. Methods: We provide a longitudinal analysis of immune responses, including immune cell phenotyping and assessments of the soluble factors present in the blood and broncho-alveolar lavage fluid (BALF) of patients at various stages of COVID-19 severity: paucisymptomatic, pneumonia and acute respiratory distress syndrome (ARDS) Results: We report an increase in soluble C5a levels proportional to COVID-19 severity and high levels of C5aR1 expression in blood and pulmonary myeloid cells, supporting a role for the C5a-C5aR1 axis in the pathophysiology of ARDS. Avdoralimab, an anti-C5aR1 therapeutic monoclonal antibodies (mAbs) prevented C5a-mediated human myeloid cell recruitment and activation, and inhibited acute lung injury (ALI) in human C5aR1 knockin mice. Conclusions: These results support the evaluation of avdoralimab to block C5a-C5aR1 axis as a mean of limiting myeloid cell infiltration in damaged organs and preventing the excessive lung inflammation and endothelialitis associated with ARDS in COVID-19 patients Acknowledgements: The Explore COVID-19 IPH group, the Explore COVID-19 Marseille Immunopole group. Ethics Approval: Human study protocol was approved by the Committee for the Protection of Persons Ile-de-France III – France (#2020-A00757-32). Animal experiments were approved by the ministere de l'enseignement superieur, de la recherche et de l'innovation – France (APAFIS#25418-2020051512242806 v2).